Nadus overlaeti (Navás, 1931) redescribed—new to the fauna of Mozambique, Namibia and Tanzania (Neuroptera: Myrmeleontidae) - Dobosz, Roland; Ábrahám, Levente; Bąkowski, Marek (Zootaxa, 2024)
Two species used to be included in the African genus Nadus: Nadus overlaeti (Navás, 1931) and Nadus sudanensis Navás, 1935. Following our revision of the genus, we propose that Nadus sudanensis Navás, 1935 (syn.nov.) should be a new junior synonym of Nadus overlaeti (Navás, 1931). The monobasic genus and species are redescribed. Several photographs illustrate morphological features. The distribution, habitat, and seasonal activity of the species are given.